1997
DOI: 10.1097/00003246-199710000-00015
|View full text |Cite|
|
Sign up to set email alerts
|

Empiric treatment of hospital-acquired lower respiratory tract infections with meropenem or ceftazidime with tobramycin

Abstract: Meropenem is well tolerated and more efficacious than the combination of ceftazidime and tobramycin for the initial empiric treatment of hospital-acquired bacterial pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 22 publications
1
78
0
4
Order By: Relevance
“…From these, 51 RCTs did not meet the inclusion criteria of the current meta-analysis for the reasons detailed in figure 1. Thus, 12 RCTs [64][65][66][67][68][69][70][71][72][73][74][75] were included in the current meta-analysis. Table 1 lists the characteristics of the 12 RCTs [64][65][66][67][68][69][70][71][72][73][74][75] included in the meta-analysis.…”
Section: Data Analysis and Statistical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…From these, 51 RCTs did not meet the inclusion criteria of the current meta-analysis for the reasons detailed in figure 1. Thus, 12 RCTs [64][65][66][67][68][69][70][71][72][73][74][75] were included in the current meta-analysis. Table 1 lists the characteristics of the 12 RCTs [64][65][66][67][68][69][70][71][72][73][74][75] included in the meta-analysis.…”
Section: Data Analysis and Statistical Methodsmentioning
confidence: 99%
“…The mean (range) quality score of the included RCTs was 2.42 (1-5), which was considered good. The quality of five RCTs [64][65][66][67]74] was high (o3), while the quality of seven [68][69][70][71][72][73]75] was low (f2). The proportion of patients under mechanical ventilation was 100% in three trials [67,68,71], .70% in five trials [64-66, 72, 74] and 50% in two RCTs [69,75], while the remaining RCTs [70,73] did not provide relevant data.…”
Section: Data Analysis and Statistical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these considerations and new data for noninfected lung tissue (14), we studied the technical feasibility of microdialysis and its ability to define the pharmacokinetic properties of antibiotics in interstitial pneumonic lung tissue in patients with pneumonia and undergoing surgery for consecutive episodes of metapneumonic empyema. The carbapenem meropenem was studied because it is a well-tolerated, broad-spectrum antibacterial agent which is well established for the empirical monotherapy of pneumonia, particularly in intensive care units (11,33), and has no significant protein binding.…”
mentioning
confidence: 99%
“…It was concluded that combination therapy using a fourth-generation cephalosporin with either an aminoglycoside or a fluoroquinolone was not associated with a clinical or biological benefit when compared with cephalosporin monotherapy for common, susceptible pathogens causing VAP [5]. Of the many comparative studies for the treatment of VAP, six are summarised in table 2 [6][7][8][9][10][11]. Perhaps the best of these studies compared imipenem alone with the combination of imipenem and netilmicin [8].…”
Section: Monotherapy Versus Combination Therapy: Comparisons Of Efficacymentioning
confidence: 99%